Ghost Story as Social Commentary: A Look at Mati Diop's Atlantics. (1st March 2021) - Hamzah, Sahar
Review of: Ghost Story as Social Commentary: A Look at Mati Diop's AtlanticsAtlantics, Mati Diop (dir.) (2019), France: Ad Vitam, France